Exercise Induced Adipokine Changes and the Metabolic Syndrome - Saeid Golbidi; Ismail Laher (Journal of Diabetes Research)
The lack of adequate physical activity and obesity created a worldwide pandemic. Obesity is characterized by the deposition of adipose tissue in various parts of the body; it is now evident that adipose tissue also acts as an endocrine organ capable of secreting many cytokines that are though to be involved in the pathophysiology of obesity, insulin resistance, and metabolic syndrome. Adipokines, or adipose tissue-derived proteins, play a pivotal role in this scenario. Increased secretion of proinflammatory adipokines leads to a chronic inflammatory state that is accompanied by insulin resistance and glucose intolerance. Lifestyle change in terms of increased physical activity and exercise is the best nonpharmacological treatment for obesity since these can reduce insulin resistance, counteract the inflammatory state, and improve the lipid profile. There is growing evidence that exercise exerts its beneficial effects partly through alterations in the adipokine profile; that is, exercise increases secretion of anti-inflammatory adipokines and reduces proinflammatory cytokines. In this paper we briefly describe the pathophysiologic role of four important adipokines (adiponectin, leptin, TNF-α, and IL-6) in the metabolic syndrome and review some of the clinical trials that monitored these adipokines as a clinical outcome before and after exercise.